OPTIMIZATION OF MEASURES TO INCREASE THE LIQUIDITY OF THE ENTERPRISE - Pistunov, Igor; Kravchenko, Olga (SWorld-Ger Conference proceedings, 2025)
An economic and mathematical model was developed to identify key factors influencing the liquidity of the enterprise. Using correlation and other types of analysis, an assessment of the parameters and data system of the model of the influence of various f